FEATURES OF INDUSTRIALIZATION IN THE USSR (1928-1930s): THE USE OF PRE-REVOLUTIONARY INDUSTRIAL POTENTIAL AND THE CREATION OF NEW SOCIALIST ENTERPRISES (ON THE EXAMPLE OF THE KLINTSOVSKY DISTRICT OF THE WESTERN REGION) - Kochergina M.V. (Вестник Брянского государственного университета)
The article reveals the possibility of using the pre-revolutionary industrial potential for the restoration, reconstruction, and commissioning of former enterprises of the cloth and match industry in the Western region, created by Old Believers and co-religionists in the XIX-early XX century in the Russian Empire, then belonging to the territory of the northern counties of Chernihiv province. In the Soviet period (late 1920-1930), due to the change in the administrative and territorial division, they became part of the Western Region of the RSFSR. The course towards industrialization, taken by the XIV Congress of the CPSU (b), assumed the creation of a strong, powerful industrial state in the Country of the Soviets, not inferior in its potential to Western countries. To this end, there was a change in the administrative and territorial division within the country, the creation of districts uniting several regions into a single industrial area. This was the Klintsovsky district of the Western region, which assumed not only the creation of new industrial enterprises, but also in nd the restoration and reconstruction of the former ones. Reliance on internal reserves, loans from the population, and the training of their own personnel should have contributed to the transformation of the backward Western region into an agrarian-industrial one. In the post-war period, factories built by Old Believers and co-religionists became new industrial socialist enterprises, the basis of the industrial potential of the southwestern districts of the Bryansk region in 1930-1980.